Cytosolic Phosphoenolpyruvate Carboxykinase Deficiency: Cause of Hypoglycemia-Induced Seizure and Death - Becker, Johanna; Haas, Nikolaus A.; Vlaho, Stefan; Heineking, Beatrice; Wortmann, Saskia B.; Rabenhorst, Dorothée; Thomas, Clara; Brunet, Theresa (Neuropediatrics, 2021)
Cytosolic phosphoenolpyruvate carboxykinase (PEPCK) deficiency (MIM 261680, EC 4.1.1.32, encoded by PCK1) is a rare disorder of gluconeogenesis presenting with recurrent hypoglycemia, hepatic dysfunction, and lactic acidosis. We report on a previously healthy 3-year-old boy who was initially admitted under the suspicion of a febrile seizure during an upper airway infection. Diagnostic workup revealed hypoglycemia as well as a cerebral edema and ruled out an infection. After a complicated course with difficult to treat symptomatic seizures, the child died on the 5th day of admission due to progressive cerebral edema. The metabolic screening showed elevated urinary lactate and Krebs cycle intermediates in line with a primary or secondary energy deficit. Due to the unclear and fatal course, trio exome sequencing was initiated postmortem (“molecular autopsy”) and revealed the diagnosis of cytosolic PEPCK deficiency based on the compound heterozygosity of a known pathogenic (c.925G > A, p.(Gly309Arg)) and a previously unreported (c.724G > A, p.(Gly242Arg)) variant in PCK1 (NM_002591.3). Sanger sequencing ruled out the disease and carrier status in three older brothers. Molecular autopsy was performed due to the unclear and fatal course. The diagnosis of a cytosolic PEPCK deficiency not only helped the family to deal with the grief, but especially took away the fear that the siblings could be affected by an unknown disease in the same manner. In addition, this case increases the genetic and phenotypic spectrum of cytosolic PEPCK deficiency.
Keywords: seizure; genetic autopsy; molecular autopsy; unexplained death; fatal hypoglycemia; PEPCK deficiency